Intrasulcular Restorations of Anterior Teeth According to the BAIR Technique: Evaluation of Periodontal Parameters - Luca Giachetti; Francesca Cinelli; Michele Nieri (MDPI AG, 2022)
Some clinical situations, such as the closure of pronounced diastemas, and the transformation of malformed, small, or peg-shaped teeth, require a rebalancing of dental proportions accompanied by a modification of the gingival contour. A traditional treatment plan can include surgical, prosthetic, and/or orthodontic treatments. In some cases, it can be considered too invasive, and not all patients are willing to undertake long therapies. To overcome these limitations, a possible solution could be the application of the Biologically Active Intrasulcular Restoration (BAIR) technique, which allows us to modify the natural emergence tooth profile using simple intrasulcular direct restorations. The aims of this paper are to investigate possible effects on gingival health, and to assess the patient satisfaction about the aesthetic intervention performed. Periodontal data were collected, and patient satisfaction was registered using the VAS questionnaire. All sites healed without complications, no adverse events were registered or reported by the patients, and no signs of periodontal morbidity were visible. The results show that the patients evaluated the final aesthetics in a positive way, and they perceived a good condition of periodontal health as well. The intervention is felt as almost painless, and patients do not report significant post-operative distress. In conclusion, the BAIR technique can provide a valid therapeutic alternative for patients for whom traditional treatments are not indicated. It is a minimally invasive intervention where both the operating times and the biologic and economic costs are reduced.